The role of Pentraxin-3 and Angiopoietin-1 in the inflammation pathway in chronic kidney disease (Annals of Medical Research, 2022)
Aim: Angiopoetin-1 and Pentraxin-3 are new generation biomarkers in the inflammation pathway that have been studied in CKD and other inflammatory diseases. This study aims to investigate the relationship of Pentraxin-3 and Angiopoetin-1 in the inflammation pathway in chronic kidney disease (CKD).Materials and Methods: Our study was planned single-center, prospective, cross-sectional study. This study includes 25 healthy volunteers, 29 predialysis cases, 34 cases in routine hemodialysis program.Blood was drawn after 12 hours of fasting. In addition to routine biochemical tests, Pentraxin-3 Angiopoetin-1, 1,25 hydroxy Vitamin D levels were measured. Age and gender parameters, BUN, creatinine, e-GFR values of the cases were recorded.Results: Pentraxin-3 levels were not statistically significant for all three groups (p=0.993).For angiopoietin-1 levels, statistical significance was found between all three groups (p
Keywords: Chronic Kidney Damage; Inflammation; Pentraxin-3; Angiopoietin-1